THE INFLUENCE OF SELF-IMAGE CONGRUENCE, HEDONIC MOTIVATION, AND BRAND EXPERIENCE ON PURCHASE INTENTION WITH BRAND ATTACHMENT AS A MEDIATING VARIABLE (STUDY ON THE INTEREST IN BYD SEAL ELECTRIC CARS IN PURWOKERTO) - Ihtiar Febrian Putra Nur Akhiddianto; Herni Justiana Astuti; Muchammad Agung Miftahuddin; Fatmah Bagis (International Journal Management and Economic, 2025)
The problem of carbon emissions from the transportation sector continues to increase globally and nationally, driving a shift in trends towards the use of more environmentally friendly electric vehicles. However, the adoption of electric cars in Indonesia still faces various challenges, including the dominance of fossil-fueled vehicles and low consumer emotional attachment to new brands. This study aims to analyze the influence of self-image congruence, hedonic motivation, and brand experience on purchase intention with brand attachment as an intervening variable, in the context of potential consumers of the BYD SEAL brand electric vehicle in the Purwokerto area. This study uses a quantitative approach with a survey method, where data were collected from 160 purposively selected respondents. The analysis technique used is Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results show that self-image congruence and brand experience have a significant positive effect on brand attachment, while hedonic motivation has no significant effect. Furthermore, purchase intention is significantly influenced by hedonic motivation and brand attachment, but not directly by self-image congruence or brand experience. Brand attachment has been shown to mediate the relationship between self-image congruence and brand experience on purchase intention, but not the relationship between hedonic motivation and purchase intention. This finding supports the Stimulus–Organism–Response (SOR) theoretical framework and emphasizes the importance of emotional attachment to the brand in shaping consumers' purchase intention for electric vehicles.